Sustainability of Fish Fillet Processing Industries in Batang District - Astrid Fauzia Dewinta; Widodo Farid Ma’ruf (Jurnal Ilmiah Perikanan dan Kelautan)
Highlights • Sustainability index from fish fillet industry is important to know because a fishing industry just not looking for feasibility study in economic dimension but all dimension (resources, technology, social, legal and institutional) • Multidimension sustainability index from fish fillet processing industry in Batang is included in the category of “Self Sustainable” with a value of 50.39 • The dimensions causes of the low sustainability in fish fillet industry are social, legal and institutional, and technology with the value of each dimension that is 48.6; 40.27; 48.9 in means “less sustainable”